Invasive Alien Plants of Himachal Pradesh, India - Chandra Sekar, K.; Pandey, Aseesh; Srivastava, S. K.; Giri, Lalit (Indian Forester, 2015)
The present paper deals with the invasive alien plants found in the state of Himachal Pradesh, India. A total number of 125 invasive alien species under 83 genera, belonging to 39 families have been recorded based on field observations, herbarium and literature consultation. Tropical American elements contribute 75% of alien species found in the state. Among the invasive, annuals comprise 63%, herbs constitute 79% and only four tree species recorded as invasive species. Invasive species based habitat shows that 44% of invasive species were most abundant in wasteland, while cultivated fields, roadsides and forests were preferred by 20, 16 and 9% species respectively. Among the invasive alien elements, 70 species (56%) are being used by local inhabitants for different medicinal uses. Early detection and monitoring of naturalized weeds are essential for better control.